Do borrower rights improve borrower outcomes? Evidence from the foreclosure process - Kristopher Gerardi; Lauren Lambie-Hanson; Paul S. Willen (Federal Reserve Bank of Atlanta, 2012)
We evaluate the effects of laws designed to protect borrowers from foreclosure. We find that these laws delay but do not prevent foreclosures. We first compare states that require lenders to seek judicial permission to foreclose with states that do not. Borrowers in judicial states are no more likely to cure and no more likely to renegotiate their loans, but the delays lead to a build-up in these states of persistently delinquent borrowers, the vast majority of whom eventually lose their homes. We next analyze a “right-to-cure” law instituted in Massachusetts on May 1, 2008. Using a difference-indifferences approach to evaluate the effect of the policy, we compare Massachusetts with neighboring states that did not adopt similar laws. We find that the right-to-cure law lengthens the foreclosure timeline but does not lead to better outcomes for borrowers.
Keywords: G21; K11; R31; 330; foreclosure; mortgage; judicial; power of sale; right to cure; Finanzmarkt; Kapitalmarktrecht; Kreditgeschäft; Gläubigerschutz; Zwangsvollstreckung; USA